The CCCTB option an experimental study - Claudia Keser; Gerrit Kimpel; Andreas Oestreicher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The objective of this paper is to look into the probability that, given the choice, corporate groups would opt for taxation on a consolidated basis. Consolidation would allow them to offset losses crossborder but remove the opportunity to exploit international tax-rate differentials between entities via transfer pricing. We present a laboratory experiment in which we investigate to what extent a corporation would be inclined to take up the consolidation option and how this would impact on the corporation s location of investment and its transfer pricing activities involving locations outside the consolidated group. We use a 2-by-2 treatment design with two levels of tax-rate differential between two investment locations, and two different remuneration functions allowing the participants to act as owners or managers of a company.
Keywords: C91; H25; M41; 330